In vitro Antioxidative Profiling of Different Fractions of Dendrocalamus strictus (Roxb.) Nees leaf Extracts - Goyal, Arvind Kumar; Middha, Sushil Kumar; Sen, Arnab (Free Radicals and Antioxidants)
Introduction: Plant derived natural antioxidants have attracted scientists for many years because of their economic viability and virtually no side effects. Therefore the present study was planned to evaluate the antioxidant activity of the leaf of Dendrocalamus strictus (Roxb.) Nees, used as household therapy for cold, cough and fever, extracted with different solvents of increasing and decreasing polarity such as water (DAQE), acetone (DAE) and methanol (DME). Methods: The antioxidant profiling of the leaf extracts was done at varying concentrations (20-200 µg/ml), using different assays like 2,2-diphenyl-1-picryl-hydrazyl (DPPH) radical scavenging activity, reducing power assay and hydrogen peroxide radical scavenging activity along with their total phenolic and flavonoid contents. Results: DME had more antioxidant activity than other extracts. Total phenol and flavonoid content were highest in the DAQE and DME fraction (112.10 ± 11.21 mg GAE/g and 199.20 ± 19.92 mg QE/g) respectively. This result also suggests a close relationship among total phenolic content, flavonoids and antioxidant activity. Conclusion: The study shows that leaf of Dendrocalamus strictus is a potential source of useful natural antioxidants, which substantiates its use as herbal remedies.
Keywords: Antioxidant; Correlation; Dendrocalamus strictus; DPPH; FRP; Reducing power